Primary Gastric Tuberculosis in an Immunocompetent Patient: The Truth Lying beneath the Surface - Fábio Pereira Correia; Luísa Martins Figueiredo; Luís Carvalho Lourenço; Sofia Santos; Rita Theias Manso; David Horta (GE: Portuguese Journal of Gastroenterology, 2023)
Gastrointestinal tuberculosis is an uncommon entity, in which clinical presentation can be widely variable, from mild and nonspecific symptoms to an acute abdomen and gastrointestinal bleeding. Gastric involvement by Mycobacterium tuberculosis is rare, especially when it occurs without other recognized infectious foci – primary gastric tuberculosis – with only a few reported cases. Endoscopic findings can be very heterogeneous, from areas of hyperemia to pseudotumor lesions. We present a case of primary gastric tuberculosis in an immunocompetent patient, in which the absence of an epidemiological context and nonspecific endoscopic findings led to a delay in the diagnosis. Bite-on-bite biopsies proved to be essential, allowing to obtain samples from deeper layers of the submucosa where M. tuberculosis was identified. This case aimed to increase awareness for this entity, especially in endemic countries or regions with a high prevalence of tuberculosis since the diagnosis is based mainly on a high index of suspicion.